Atomic structure of grain boundaries for layered molybdenum disulfide (MoS2) - Cheah, Shun Yee (Nanyang Technological University, 2020)
A study on the atomic structure characterization of grain boundary for monolayered molybdenum disulphide (MoS2) by using aberration-corrected scanning transmission electron microscope (STEM) techniques. The MoS2-MoSe2 heterostructure thin film on silicon wafer are firstly grown by chemical vapour deposition (CVD) method. Then, the MoS2-MoSe2 thin film sample used for annular dark field (ADF)-STEM imaging is transferred from silicon substrate to an Au TEM grid by using PMMA and 20% KOH in the experiment. Different configurations of grain boundary in monolayer and multi-layer structure are observed and discussed (straight channel, wending channel, point defects, and stitched grain staking). Thought the knowledge developed in this study may help to get insight into the factors which causing the properties changes of the material.